A two-dimensional organic material based on a porphyrin unit and a preparation method and application thereof
Patent Information
- Application Number
- CN202611287328.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-08-24
AI Technical Summary
Existing porphyrin-based materials tend to aggregate randomly during synthesis, photo-driven reduction relies on sacrificial agents, and they exhibit poor selectivity in complex multi-metal leaching solutions, making it difficult to achieve efficient and green gold recovery.
Two-dimensional nanosheets with ordered interlayer stacking structures were formed by the self-assembly of protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin and pyromellitic acid in pure aqueous phase. The selective enrichment and in-situ reduction of tetrachloroaurate anions were carried out by using visible light to drive photogenerated charges.
It achieves highly selective and high-capacity gold recovery from complex electronic waste leachates, avoiding organic solvents and external electron sacrificial agents, simplifying the process and reducing the risk of environmental pollution.
Smart Images

Figure CN122832311B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of two-dimensional organic materials technology, specifically to a two-dimensional organic material based on porphyrin units, its preparation method, and its application. Background Technology
[0002] Two-dimensional ultrathin nanomaterials, due to their extremely high specific surface area and highly exposed surface active sites, have shown far greater potential than three-dimensional bulk materials in photocatalysis and adsorption separation. Coleman et al. first obtained single-atom-layer graphene from graphite through liquid-phase exfoliation, pioneering the exfoliation paradigm of "layered crystals → two-dimensional nanosheets" (Accounts of Chemical Research, 2013, 46, 14-22). However, extending this paradigm to organic supramolecular crystals with photosensitive and coordination activities faces fundamental difficulties: the interlayers of layered organic crystals are maintained by multiple strong non-covalent interactions such as π-π stacking and hydrogen bond networks. Existing exfoliation methods heavily rely on high-boiling-point, highly toxic organic solvents and surfactants to overcome interlayer forces and suppress folding. Hu et al. systematically summarized this field, pointing out that the liquid-phase exfoliation of most non-graphene two-dimensional materials relies on the assistance of dispersants or surfactants to achieve stable dispersion (Nanoscale, 2021, 13, 460-484). Whether the controlled two-dimensional self-assembly of organic supramolecular crystals can be achieved in a pure aqueous phase without the addition of any surfactants, while maintaining their long-range ordered crystalline stacked structure, remains an unsolved technical problem in the field.
[0003] Gold, due to its excellent electrical conductivity and chemical stability, is widely used in the electronics, pharmaceutical, and chemical industries. The gold grade in electronic waste can be 25 to 250 times that of natural ore. Achieving efficient and selective recovery of gold from wet leaching solutions is a key pathway to alleviate the precious metal resource crisis. However, actual leaching solutions contain Au(III) coexisting with high concentrations of base metal ions such as Cu(II) and Ni(II), resulting in an extremely complex composition. Photocatalysis technology can be used to recover gold from AuCl4. -In-situ reduction to elemental gold enables green recovery without the need for external chemical reducing agents. Porphyrins, with their 18π-electron macrocyclic conjugated structure, possess both broad-spectrum light-harvesting capabilities and rich coordination chemistry, making them ideal building blocks for light-driven gold recovery. However, existing porphyrin-based materials face three major bottlenecks: (1) Synthesis requires organic solvents and the products have poor crystallinity—the strong π-π stacking tendency of porphyrins easily leads to disordered aggregation in conventional synthesis. For example, the porphyrin-phenazine porous polymer (COP-180) reported by Nguyen et al. has an adsorption capacity of 1.354 g / g for Au(III), but it is an amorphous structure, lacks ordered charge transport channels, and is highly dependent on high-energy ultraviolet light excitation (Chemistry of Materials, 2020, 32, 5343-5349); (2) Photo-driven reduction depends on sacrificial agents—for example, Shu et al. used porphyrin-based Zr-MOF (PCN-224) to achieve visible light-enhanced gold recovery, but acetic acid must be added as an electron sacrificial agent to capture photogenerated holes in order to achieve a higher capacity (ACS ES&T Engineering, 2023, 3, (1042-1052); (3) There is insufficient evidence of high selectivity in complex polymetallic leachates. Summary of the Invention
[0004] The purpose of this invention is to address the common technical problems of low adsorption capacity, poor selectivity, and easy recombination of photogenerated carriers in existing gold recovery adsorption materials, and to provide a two-dimensional organic material based on porphyrin units, its preparation method, and its applications. This two-dimensional organic material possesses unique single-layer, double-layer, and few-layer ultrathin two-dimensional nanosheet structures, along with a highly crystalline ordered stacked structure. The preparation process is simple and the raw material cost is low. In complex electronic waste leachate systems, no additional electron sacrificial agent is required; ultra-high selective enrichment and rapid in-situ reduction of tetrachloroaurate anions can be achieved solely through visible light-driven processes.
[0005] The above-mentioned objective of the present invention is achieved through the following technical solution: The first aspect of the present invention provides a two-dimensional organic material, wherein the two-dimensional organic material is a two-dimensional nanosheet formed by supramolecular self-assembly of protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin (TAPP) and pyromellitic acid.
[0006] Furthermore, the supramolecular interactions include intermolecular hydrogen bonds and π-π interactions.
[0007] Furthermore, the two-dimensional organic material is a two-dimensional nanosheet with an ordered interlayer stacking structure, and the X-ray diffraction pattern shows characteristic diffraction peaks corresponding to π-π stacking.
[0008] Furthermore, the two-dimensional organic material includes single-layer two-dimensional nanosheets, double-layer two-dimensional nanosheets, and a few (3-10) layers of two-dimensional nanosheets; the thickness of the single-layer two-dimensional nanosheets is 1.3-2.0 nm, the thickness of the double-layer two-dimensional nanosheets is 3.0-4.0 nm, and the lateral dimension of the two-dimensional organic material is 10-20 μm.
[0009] Furthermore, the two-dimensional organic material has a complete periodic lattice structure and exhibits high crystallinity with single-crystal characteristics.
[0010] Furthermore, the optical band gap of the two-dimensional organic material is 1-2 eV, preferably 1.40 eV.
[0011] A second aspect of the present invention provides a method for preparing the two-dimensional organic material described in the first aspect, comprising the following steps: (1) Dissolve 5,10,15,20-tetra(4-aminophenyl)porphyrin in an acid solution, wherein the concentration of 5,10,15,20-tetra(4-aminophenyl)porphyrin in the acid solution is 0.8-1.2 mg / mL, to obtain a protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin solution; dissolve pyromellitic acid in water to obtain a pyromellitic acid aqueous solution with a concentration of 0.8-1.2 mg / mL; (2) The protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin solution, the pyromellitic acid aqueous solution and water are mixed at a volume ratio of (1.3-1.4):1:(97-100) and self-assembled at 48-52 °C to obtain the two-dimensional organic material.
[0012] In the process of preparing two-dimensional organic materials, no surfactants or steric regulators are added. Instead, the concentration of the precursor (protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin solution) is reduced and the pH of the system is appropriately increased in pure aqueous phase. Through low-concentration restricted self-assembly, stable two-dimensional ultrathin nanosheets are directly obtained.
[0013] Further, in step (1), the acid is hydrochloric acid; the concentration of the acid solution is 0.10-0.14 mol / L.
[0014] The third aspect of this invention provides an application of the two-dimensional organic material described in the first aspect in gold recovery, which can selectively recover gold from gold-containing waste liquid.
[0015] The two-dimensional organic material provided by this invention, when excited by visible light, can effectively generate photogenerated charges and directly drive the in-situ reduction of tetrachloroaurate anions. Through this synergistic mechanism of "photo-driven adsorption-in-situ reduction", ultra-high capacity and high selectivity gold extraction can be achieved in a single step from gold-containing waste liquids (such as leachates from complex electronic waste).
[0016] A fourth aspect of the present invention provides a method for recovering gold from a gold-containing solution using the two-dimensional organic material described in the first aspect, comprising the following steps: S1. The two-dimensional organic material is mixed with a gold-containing solution and subjected to an adsorption-reduction synergistic reaction under visible light irradiation. Under photoexcitation, the two-dimensional organic material uses photogenerated electrons to reduce the specifically bound tetrachloroaurate anions to elemental gold in situ and deposit it on the surface of the two-dimensional organic material. S2. Solid-liquid separation is performed on the two-dimensional organic material deposited with elemental gold to separate and extract the elemental gold, thereby realizing the recovery of gold.
[0017] The two-dimensional organic material provided by this invention uses porphyrin units as photoactive centers and specific adsorption sites for gold. In gold-containing solutions (such as leachates from complex electronic waste), without the need for external electron sacrificial agents, the material itself consumes photogenerated holes and selectively enriches and reduces tetrachloroaurate anions in situ under visible light to generate elemental gold.
[0018] The gold recovery method of this invention involves reacting under visible light for 60-90 min, achieving a gold recovery rate ≥99% in solutions containing tetrachloroaurate anions. The reduced elemental gold is epitaxially grown on the surface of a two-dimensional organic material to form a hexagonal sheet-like structure, and the elemental gold exhibits an electron-rich state. The equilibrium adsorption capacity of the two-dimensional organic material provided by this invention for elemental gold is 10500-11500 mg / g.
[0019] Furthermore, in step S1, the pH value of the gold-containing solution is 2-7.
[0020] Furthermore, in step S1, the gold-containing solution is an electronic waste leachate or gold-containing industrial wastewater.
[0021] Furthermore, in step S1, the gold-containing solution contains both copper and nickel ions; after reacting under visible light for 60-90 min, the removal rates of both copper and nickel ions are less than 10%, demonstrating high ion selectivity.
[0022] Furthermore, in step S1, the wavelength of the visible light is 400-800 nm.
[0023] Further, in step S1, the illuminance of the visible light is 10-100 mW / cm². 2 .
[0024] Furthermore, in step S2, after solid-liquid separation, the two-dimensional organic material deposited with elemental gold (i.e., the gold-loaded composite product) can be removed by calcination to obtain elemental gold.
[0025] The above-described technical solution of the present invention has the following beneficial effects: 1. This invention successfully prepared a two-dimensional organic material using protonated TAPP and pyromellitic tetracarboxylic acid as building blocks through confined self-assembly in a pure aqueous phase. This two-dimensional ultrathin nanosheet uses porphyrin units as both photocatalytic active centers and specific adsorption sites. Its excellent optical band gap (1.40 eV) enables it to strongly absorb visible and even near-infrared light. Simultaneously, its two-dimensional ultrathin structure significantly shortens the transport distance of photogenerated charges from the interior to the surface, effectively suppressing bulk recombination of photogenerated carriers. Under visible light excitation, the effectively separated photogenerated electrons can rapidly transfer to the nanosheet interface, providing ample electron reserves and efficient transfer channels for the in-situ reduction of targeted tetrachloroaurate anions, achieving a green gold extraction process without the need for external electron sacrificial agents.
[0026] 2. The two-dimensional organic material provided by this invention can recover gold from gold-containing solutions under visible light irradiation. The equilibrium adsorption capacity of the two-dimensional organic material is as high as 11204 mg / g, which is more than 10 times that under light-shielded conditions, and a gold recovery rate of over 99% can be achieved within 90 minutes. Simultaneously, this two-dimensional organic material exhibits excellent selective recognition ability for tetrachloroaurate anions and strong resistance to interference from coexisting Cu and Ni impurities: in a simulated electronic waste leaching system, even with coexisting Cu... 2+ (2727.5 mg / L) and Ni 2+ Despite the presence of numerous base metal impurities such as (131.13 mg / L), gold can still be selectively recovered, while the removal rates of copper and nickel ions (ion reduction rates in solution) are only 6.59% and 9.73%, respectively, achieving one-step targeted enrichment of gold in complex systems.
[0027] 3. The entire process of preparing the two-dimensional organic material and recovering gold in this invention is completed under aqueous phase and visible light driving conditions, without the need for any surfactants, steric precipitators, or external electron sacrificial agents. The synthesis conditions are mild, avoiding the secondary pollution risks caused by the volatilization of organic solvents and the use of toxic reagents in traditional processes. In the recovery reaction, the reduced gold is selectively enriched on the surface of the two-dimensional material in the form of regular hexagonal nanosheets. This supported state of elemental gold has a low impurity content, greatly simplifying and facilitating subsequent gold refining processes. The process of this invention is simple, environmentally friendly, and has good prospects for industrial application. Attached Figure Description
[0028] Figure 1This is a schematic diagram illustrating the synthesis of the two-dimensional organic material prepared in Example 1.
[0029] Figure 2 The images show the morphology and thickness characterization of the two-dimensional organic materials prepared in Example 1. Among them, (a) is the atomic force microscopy (AFM) morphology image and corresponding height profile of a single-layer two-dimensional organic nanosheet, (b) is the AFM morphology image and height profile of a double-layer two-dimensional organic nanosheet, (c) is the AFM morphology image and height profile of a few-layer two-dimensional organic nanosheet, and (d) is the scanning electron microscope (SEM) image of the two-dimensional organic nanosheet.
[0030] Figure 3 The image shows the structural characterization of the two-dimensional organic material prepared in Example 1; where (a) is a high-resolution transmission electron microscope (HRTEM) image, (b) is a transmission electron microscope (TEM) image, (c) is the corresponding selected area electron diffraction (SAED) pattern, and (d) is the X-ray diffraction (XRD) pattern of 2DOM, PMA, and TAPP.
[0031] Figure 4 The optical properties characterization diagrams of the two-dimensional organic material prepared in Example 1 are shown below; where (a) is the ultraviolet-visible absorption (UV-Vis ABS) spectrum and (b) is the optical bandgap fitting curve obtained by converting the UV-Vis ABS spectrum.
[0032] Figure 5 The image shows the SEM image of the two-dimensional organic material prepared in Comparative Example 1; the left icon has a bar of 1 μm and the right icon has a bar of 500 nm.
[0033] Figure 6 SEM images of the two-dimensional organic materials prepared in Comparative Examples 2-6 are shown; where (a) is Comparative Example 2, (b) is Comparative Example 3, (c) is Comparative Example 4, (d) is Comparative Example 5, and (e) is Comparative Example 6.
[0034] Figure 7 The thermogravimetric-derivative thermogravimetric (TG-DTG) curve of the two-dimensional organic material prepared in Example 1 is shown.
[0035] Figure 8 The images show the suspensions obtained by dispersing the two-dimensional organic material prepared in Example 1 in aqueous solutions with different pH values (1-13) and the Zeta potential distribution diagram of the fresh suspension; where (a) is the fresh suspension, (b) is the suspension after standing for 1 day, (c) is the suspension after standing for 10 days, and (d) is the Zeta potential diagram of the fresh suspension.
[0036] Figure 9The images show the suspensions obtained by dispersing the two-dimensional organic material prepared in Example 1 in different organic solvents (ethanol (EtOH), N,N-dimethylformamide (DMF), acetonitrile (MeCN), acetone (ACE), tetrahydrofuran (THF), toluene (PhMe), and dichloromethane (DCM)); where (a) is the freshly prepared suspension, (b) is the suspension after standing for 1 day, and (c) is the suspension after standing for 1 day under laser pen illumination.
[0037] Figure 10 The graph shows the macroscopic recovery performance of the two-dimensional organic material prepared in Example 1 for tetrachloroaurate anions; where (a) is a comparison graph of equilibrium adsorption amount under light and dark conditions, (b) is the time-reduction rate kinetic curve under light and dark conditions, and (c) is the selective recovery test result graph of the multi-metal coexistence system.
[0038] Figure 11 The image shows the characterization of the gold-loaded composite product obtained by in-situ reduction of tetrachloroaurate anions in the two-dimensional organic material prepared in Example 1 under visible light driving; where (a) is the SEM image of the composite product, (b) is the XRD pattern of the composite product, (c) is the high-resolution X-ray photoelectron spectroscopy (XPS) spectrum of Au in the composite product, and (d) is the TG-DTG curve of the composite product. Detailed Implementation
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0040] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0041] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.
[0042] Example 1 A method for preparing a two-dimensional organic material includes the following steps: (1) Mix concentrated hydrochloric acid with deionized water to prepare a dilute hydrochloric acid aqueous solution with a concentration of 0.12 mol / L; weigh TAPP and dissolve it in the dilute hydrochloric acid aqueous solution. The concentration of TAPP in the dilute hydrochloric acid aqueous solution is 1 mg / mL, and a protonated TAPP solution is obtained.
[0043] Alternatively, pyromellitic acid (PMA) is directly dissolved in deionized water and then sonicated to ensure complete dissolution, thus preparing an aqueous solution of pyromellitic acid with a concentration of 1 mg / mL.
[0044] (2) Add 195.3 mL of deionized water to the reaction vessel, then add 2.7 mL of protonated TAPP solution and stir to mix thoroughly. Under stirring at room temperature, slowly add 2 mL of pyromellitic acid aqueous solution to the mixture. After the addition is complete, place the system in a 50 ℃ oven and let it stand for 8 h. During the reaction, electrostatic attraction-dominated pre-assembly occurs in the system, and the precipitate is spontaneously assembled through the intermolecular hydrogen bond network and the π-π interaction between the porphyrin ring. The synthesis schematic diagram is shown below. Figure 1 As shown.
[0045] After the reaction was completed, the mixture was centrifuged to collect the solid precipitate. The solid precipitate was washed three times with deionized water. After washing, the solid was dried in a vacuum drying oven to obtain a two-dimensional organic material, denoted as 2DOM.
[0046] The synthesis process in this embodiment is carried out entirely in a pure aqueous phase without the addition of any surfactants, and the preparation conditions are mild and environmentally friendly.
[0047] The two-dimensional organic material prepared in Example 1 was diluted in water to prepare a low-concentration homogeneous dispersion (0.01 mg / mL). Then, 20 μL of the dispersion was dropped onto the center of a clean and smooth Si / SiO2 substrate. A spin-coating process was used (spin speed set at 2000 rpm, spin-coating for 30 s), utilizing centrifugal force to evenly spread the droplet on the substrate surface. Finally, the substrate was allowed to air dry at room temperature, and AFM was used for observation. The observation results are as follows: Figure 2 As shown, the two-dimensional organic material prepared in Example 1 includes single-layer two-dimensional organic nanosheets, double-layer two-dimensional organic nanosheets, and a few-layer two-dimensional organic nanosheets. The thickness of the double-layer two-dimensional organic nanosheets is approximately 3.8 nm. This intrinsically grown multi-level ultrathin thickness distribution not only confirms the highly anisotropic two-dimensional growth orientation of the material, but this two-dimensional structure also endows the material with a high specific surface area and fully exposed photocatalytic active sites.
[0048] SEM images of the two-dimensional organic materials prepared in Example 1 are shown below. Figure 2 As shown in (d), the two-dimensional organic material exhibits a typical and regular two-dimensional ultrathin nanosheet morphology, with a large lateral area and a smooth and flat surface.
[0049] The morphology and structure characterization of the two-dimensional organic material prepared in Example 1 are as follows: Figure 3As shown, TEM images visually confirm the intrinsic two-dimensional nanosheet morphology of the material; clear lattice fringes with a spacing of 0.67 nm are observed in HRTEM images, and combined with the regular diffraction spots in the corresponding SAED pattern, fully demonstrating that the two-dimensional nanosheets have a highly ordered crystalline structure. Furthermore, its XRD pattern shows two distinct characteristic diffraction peaks, further confirming its good crystallinity, which is mainly attributed to the tight and ordered π-π stacking between the internal porphyrin units.
[0050] The light absorption properties of the two-dimensional organic material prepared in Example 1 are as follows: Figure 4 As shown, the UV-Vis ABS spectrum reveals that this two-dimensional organic material exhibits significant absorption across the entire visible light range of 400-800 nm, extending into the near-infrared band, forming a continuous, broad-spectrum, strong absorption band. This broad-spectrum visible light capture capability significantly improves the utilization rate of solar energy. The material can stably generate long-lived photogenerated carriers upon photoexcitation, enabling AuCl4 to achieve [further absorption / transfer] via ultrafast interfacial charge transfer. - Specific adsorption and in-situ reduction provide an excellent optical basis and micro-dynamic conditions for the highly selective and large-capacity photo-driven recovery of tetrachloroaurate anions from complex electronic waste leachates.
[0051] Comparative Example 1 A method for preparing a two-dimensional organic material includes the following steps: (1) Mix concentrated hydrochloric acid with deionized water to prepare a dilute hydrochloric acid aqueous solution with a concentration of 0.12 mol / L; weigh 5,10,15,20-tetra(4-pyridyl)porphyrin (TPyP) and dissolve it in the dilute hydrochloric acid aqueous solution. The concentration of TPyP in the dilute hydrochloric acid aqueous solution is 1 mg / mL, and a protonated TPyP solution is obtained.
[0052] Alternatively, pyromellitic acid is directly dissolved in deionized water and then sonicated to ensure complete dissolution, thus preparing a pyromellitic acid aqueous solution with a concentration of 1 mg / mL.
[0053] (2) Add 196.7 mL of deionized water to the reaction vessel, then add 2.7 mL of protonated TPyP solution and stir to mix evenly; under stirring at room temperature, slowly add 2 mL of pyromellitic acid aqueous solution to the mixture. After the addition is complete, place the system in a 50 ℃ oven and let it stand at a constant temperature for 8 h.
[0054] Experimental results show that, due to the fundamental differences in steric hindrance, electron cloud density, and spatial topological symmetry between the pyridinium group and TAPP, a multi-complementary strong hydrogen bond network cannot be formed between the protonated pyridinium site and the pyromellitic tetracarboxylate ion. The mixed system remained clear for a long period without spontaneous precipitation; even with prolonged reactions, only disordered one-dimensional crystals or amorphous oligomers were obtained, as shown in the SEM images. Figure 5 As shown.
[0055] Comparative Example 2 A method for preparing a two-dimensional organic material includes the following steps: (1) Mix concentrated hydrochloric acid with deionized water to prepare a dilute hydrochloric acid aqueous solution with a concentration of 0.12 mol / L; weigh TAPP and dissolve it in the dilute hydrochloric acid aqueous solution. The concentration of TAPP in the dilute hydrochloric acid aqueous solution is 1 mg / mL, and a protonated TAPP solution is obtained.
[0056] Alternatively, pyromellitic acid is directly dissolved in deionized water and then sonicated to ensure complete dissolution, thus preparing a pyromellitic acid aqueous solution with a concentration of 1 mg / mL.
[0057] (2) Add 176.5 mL of deionized water to the reaction vessel, then add 13.5 mL of protonated TAPP solution and stir to mix evenly; under stirring at room temperature, slowly add 10 mL of pyromellitic acid aqueous solution to the mixture. After the addition is complete, place the system in a 50 ℃ oven and let it stand at a constant temperature for 8 h.
[0058] Comparative Example 3 A method for preparing a two-dimensional organic material includes the following steps: (1) Mix concentrated hydrochloric acid with deionized water to prepare a dilute hydrochloric acid aqueous solution with a concentration of 0.12 mol / L; weigh TAPP and dissolve it in the dilute hydrochloric acid aqueous solution. The concentration of TAPP in the dilute hydrochloric acid aqueous solution is 1 mg / mL, and a protonated TAPP solution is obtained.
[0059] Alternatively, pyromellitic acid is directly dissolved in deionized water and then sonicated to ensure complete dissolution, thus preparing a pyromellitic acid aqueous solution with a concentration of 1 mg / mL.
[0060] (2) Add 153 mL of deionized water to the reaction vessel, then add 27 mL of protonated TAPP solution and stir to mix evenly; under stirring at room temperature, slowly add 20 mL of pyromellitic acid aqueous solution to the mixture. After the addition is complete, place the system in a 50 ℃ oven and let it stand at a constant temperature for 8 h.
[0061] Compared to Example 1, Comparative Examples 2-3 added protonated TAPP solution and pyromellitic acid aqueous solution at volumes 5 times and 10 times that of Example 1, respectively. Due to the increased precursor concentration and overall system acidity, supersaturation increased and nucleation rate became uncontrolled. After the same post-processing steps, the collected solid products showed that independently dispersed, well-defined, and regularly morphologically regular two-dimensional nanosheets rapidly cross-linked, curled, and tightly bound together, self-assembling to form uniformly sized three-dimensional flower-shaped microspheres. SEM images are shown below. Figure 6 As shown in (a) and (b).
[0062] Comparative Example 4 A method for preparing a two-dimensional organic material is basically the same as that in Example 1, except that in step (2), after the drop addition is completed, the system is placed in a refrigerator at 2 ℃ and allowed to stand for 8 h.
[0063] Comparative Example 5 A method for preparing a two-dimensional organic material is basically the same as that in Example 1, except that in step (2), after the droplet is added, the system is placed at room temperature and allowed to stand for 8 hours for reaction.
[0064] Comparative Example 6 A method for preparing a two-dimensional organic material is basically the same as that in Example 1, except that in step (2), after the drop addition is completed, the system is placed in an 80 ℃ oven and kept at a constant temperature for 8 h.
[0065] The results of Example 1 and Comparative Examples 4-6 indicate that temperature control directly determines the diffusion rate of building blocks and the macroscopic nucleation and growth behavior. At low temperatures (2 °C), the reaction kinetics of the system are too sluggish, hindering the ability of molecules to overcome energy barriers and oriented, resulting in products that are mostly fragmented, discontinuous, amorphous patches, as shown in the SEM images. Figure 6 As shown in (d), as the temperature rises to room temperature (25 °C), anisotropic growth begins to dominate, and discrete wafers emerge in the system, but they are generally small in size and still have smooth boundaries. The SEM images are shown below. Figure 6 As shown in (c), when the temperature was further optimized to 50 °C, the system reached a near-perfect thermodynamic equilibrium window for nucleation and growth, prompting molecules to undergo precise, long-range self-assembly and stacking within a strong two-dimensional supramolecular hydrogen bond network, thereby constructing regular two-dimensional nanosheets with huge areas, extremely flat surfaces, and sharp geometric edges. However, when the temperature is too high, reaching 80 °C, the excessively rapid reaction kinetics and intense high-temperature thermal motion may induce local thermodynamic fine-tuning of the crystal planes or secondary nucleation on the surface, resulting in the emergence of tiny triangular / stepped microstructural defects on the originally flat nanosheet surface, such as... Figure 6As shown in (e). In summary, 50 °C is the optimal reaction temperature for this system. Under this temperature condition, two-dimensional single-crystal nanosheets with high crystallinity, excellent anisotropy, and regular morphology can be prepared in situ.
[0066] Comparative Example 1 (Literature report: porphyrin-phenazine porous network polymer COP-180) Nguyen et al. (Chem. Mater., 2020, 32, 5343-5349) reported a porphyrin-phenazine porous network polymer (COP-180) constructed by crosslinking porphyrin and phenazine units via Friedel-Crafts alkylation. This material exhibited a saturated adsorption capacity of 1354 mg / g (1.354 g / g) for Au(III) under UV excitation, with the adsorption mechanism primarily dependent on the interaction between porphyrin pyrrole nitrogen and AuCl4. - Coordination and photogenerated electron reduction are important aspects of COP-180. However, COP-180 is an amorphous covalent organic network that lacks long-range ordered pore structures and precise controllable spatial arrangement of active sites. Photochemical reduction is highly dependent on continuous excitation by high-energy ultraviolet light, with a weak response in the visible light region. The amorphous framework lacks ordered charge transport channels, resulting in low efficiency of photogenerated electron-hole pair separation and inherent limitations on quantum yield.
[0067] Compare with Example 2 (Literature reports on porphyrin-integrated one-dimensional covalent organic framework PP-COF) Chen et al. (Angew. Chem. Int. Ed., 2024, e202419940) reported a porphyrin-integrated one-dimensional covalent organic framework (PP-COF) with an adsorption capacity of 4729 mg / g for Au(III) under visible light-driven conditions (approximately 1433 mg / g in the dark, with a light enhancement factor of approximately 3.3 times), without the need for an external sacrificial agent. However, this material has a one-dimensional chain-like COF structure, and the transport of photogenerated carriers along the one-dimensional direction is dimensionally restricted, resulting in significant anisotropy in charge migration; the synthesis process requires the use of an organic solvent system.
[0068] Comparative Example 3 (Literature report: triazaquinone covalent organic framework COF-JLU63) Liu et al. (Sci. China Chem., 2022, 65, 1757-1764) reported a two-dimensional covalent organic framework (COF-JLU63) based on hexamethoxytriazazines, which exhibits a saturated adsorption capacity of 7598 mg / g for Au(III) under photo-redox synergy, one of the highest values reported in the literature to date. However, the photoreduction mechanism of this material depends on the synergistic participation of an external photosensitizer or redox medium, rather than the material itself independently completing the entire process of light capture, charge separation, and in-situ reduction; furthermore, the light absorption range of the triazazines is concentrated in the ultraviolet-blue light region, resulting in limited utilization efficiency of the solar spectrum.
[0069] Compare with Example 4 (Literature report on COF / MoS2 composite material MoS-TpTa) Zhou et al. (Sep. Purif. Technol., 2024, 335, 126599) reported a COF / MoS2 composite material (MoS-TpTa-1.5) with an adsorption capacity of 2564.8 mg / g for Au(III), and the adsorption was completed within 5 min, exhibiting rapid adsorption kinetics. However, its synthesis requires the composite of COF and MoS2 nanosheets, which is a cumbersome preparation process, and the interfacial stability of the two components is difficult to guarantee in long-term use; moreover, the adsorption mechanism is mainly based on chemical coordination and physical adsorption, lacking a photo-driven enhancement effect.
[0070] Compare with Example 5 (traditional commercial adsorbent materials) Activated carbon typically exhibits a saturated adsorption capacity of only 34-170 mg / g for Au(III), while strong-base ion exchange resins (such as Amberjet 4400) have a capacity of approximately 428 mg / g (Kwak et al., Chem. Eng. J., 2010, 165, 440-446). These traditional materials suffer from low specific surface area and active site density, lack specific molecular recognition capabilities, and have no photoresponsive properties, making it difficult to achieve efficient and selective gold recovery in complex electronic waste leachate systems.
[0071] Test Example 1 To evaluate the thermal stability and colloidal stability of the two-dimensional organic material of the present invention under different liquid phase environments, thermogravimetric (TG) analysis and Zeta potential tests were performed on the two-dimensional organic material prepared in Example 1. The specific results are as follows: 1. Thermal stability analysis of materials The TG-DTG curve of the two-dimensional organic material prepared in Example 1 is shown below. Figure 7 As shown, the two-dimensional organic material of this invention remains stable below 180 °C, meeting the temperature requirements for liquid-phase precious metal recovery operations. Between 180 °C and 354 °C, the material exhibits an initial weight loss of approximately 9%, primarily attributed to the removal of free solvent or water of crystallization within the material, and thermally driven partial intermolecular dehydration condensation. Upon further heating to 400 °C, significant structural decomposition and weight loss occur, indicating that the critical temperature for the collapse of its core organic framework is approximately 400 °C. This result confirms that the charge-assisted hydrogen bond network assembled from TAPP and pyromellitic acid imparts excellent thermal stability to the material.
[0072] 2. Analysis of suspensions obtained by dispersing materials in aqueous solutions at different pH values and their zeta potentials. Figure 8Figure (a) shows the initial dispersion state of a two-dimensional organic material suspension with an initial concentration of 0.5 mg / mL under different acid and alkaline conditions. Figure 8 The Zeta potential data in (d) show that the colloidal dispersion stability of the material exhibits a significant pH dependence. Under strongly acidic conditions (pH=1), due to the high protonation of the amino groups in the nanosheet framework, the material partially dissolves after long-term standing, accompanied by a greening of the suspension. In a slightly acidic environment (pH=3), the system exhibits an optimal homogeneous suspension state with a high density of positive charges on the surface (Zeta potential as high as +41.5 mV). The strong electrostatic repulsion between particles ensures that the suspension remains stable after 1 day of standing. Figure 8 (b) or even 10 days Figure 8 Even after (c) it can still maintain good macroscopic dispersion stability.
[0073] When the solution is in the weakly acidic to weakly alkaline range (pH = 5-9), the Zeta potential drops sharply and remains near the isoelectric point (+1.4 ~ +2.2 mV). At this point, the protonated amino and dissociated carboxyl groups on the nanosheet surface reach a high charge equilibrium, with the net external charge approaching zero. The disappearance of electrostatic repulsion directly leads to rapid macroscopic aggregation, such as... Figure 8 As shown in (b) and (c), the suspension in this pH range showed significant flocculation and sedimentation after only 1 day of standing, and the sedimentation was more complete after 10 days of standing.
[0074] Furthermore, in alkaline to strongly alkaline environments (pH=11-13), the deprotonation of groups within the framework disrupts the charge-assisted hydrogen bond network, leading to varying degrees of skeletal decomposition and TAPP molecule precipitation. In summary, the macroscopic static behavior of the two-dimensional organic material closely matches the variation of its zeta potential with pH. This not only directly confirms that the material is formed by the cross-linking of protonated amino and deprotonated carboxyl groups via charge-assisted hydrogen bonds, but also clearly defines the optimal stable operating window of the material, providing crucial theoretical basis for its processing and application in specific acidic liquid environments.
[0075] Test Example 2 To further clarify the processing potential of the material in different polar environments, the dispersibility and colloidal stability of the two-dimensional organic material prepared in Example 1 in different organic solvents were systematically tested. The test results are as follows: Figure 9 As shown: 1. Excellent stability (DCM and THF): In dichloromethane (DCM) and tetrahydrofuran (THF), the suspension remains dark in color, with almost no macroscopic precipitation observed. This indicates that the polarity and surface tension of these two solvents are highly compatible with the two-dimensional organic materials, and their solvent molecules can effectively insert into the interlayer of nanosheets, providing sufficient steric hindrance or solvation layers. This effectively overcomes the van der Waals forces and π-π stacking interactions between nanosheets, achieving long-term stable dispersion.
[0076] 2. Moderate dispersibility (EtOH and MeCN): In ethanol (EtOH) and acetonitrile (MeCN), the suspension becomes lighter in color and translucent, with some sedimentation at the bottom. This indicates that although some larger aggregates settle, a considerable concentration of few-layer or single-layer two-dimensional organic materials remain stably suspended in the liquid phase.
[0077] 3. Poor stability (ACE and PhMe): In acetone (ACE) and nonpolar toluene (PhMe), the suspension exhibited severe aggregation and sedimentation after standing for one day, with the supernatant becoming highly transparent. This indicates that these solvents cannot provide sufficient interaction forces to maintain the dispersed state of the two-dimensional organic material framework, and the nanosheets tend to recombine and aggregate under thermodynamic drive.
[0078] 4. Structural Decomposition (DMF): In N,N-dimethylformamide (DMF), the material undergoes macroscopic structural decomposition. The microscopic mechanism of this phenomenon lies in the fact that DMF is a nonproton polar solvent with extremely strong hydrogen bond acceptance, high dielectric constant, and a certain degree of Lewis basicity. Because the core framework of 2DOM nanosheets is highly dependent on protonated amino groups (-NH3),... + ) and pyromellitic acid (-COO) - The DMF framework is maintained by a "charge-assisted hydrogen bond network" between molecules. When DMF is introduced into the DMF system, the high concentration of DMF molecules, with their strong electron-donating ability of carbonyl oxygen, competitively binds with the protonated amino groups within the framework, thus violently breaking the original intermolecular hydrogen bonds. Simultaneously, the basic nature of DMF induces local deprotonation, completely disintegrating the electrostatic crosslinking hubs within the nanosheets. The collapse of this dual effect of electrostatic and hydrogen bonding ultimately leads to the thermodynamic instability and complete disintegration of the supramolecular framework.
[0079] Test Example 3 The light-driven single-cycle recovery performance and ion selectivity of the two-dimensional organic material prepared in Example 1 were tested. The test methods and results are as follows: 1. Gold recovery capacity test In tetrachloroaurate solutions with different initial gold concentrations, light-shielded and visible light (CEL-S500 light source, 100 mW / cm²) were respectively set up. 2Two groups were irradiated for performance comparison tests: 2 mL of an aqueous solution (pH 3) containing the two-dimensional organic material prepared in Example 1 with a concentration of 0.4 mg / mL was added to 50 mL of potassium chloroaurate aqueous solutions with a series of initial concentrations. A light-protected control group and a visible light irradiation experimental group were simultaneously set up. After the reaction reached stability for 8 h, the gold recovery performance of each system was measured. The gold recovery per unit mass of material was calculated based on the initial mass of the two-dimensional organic material, excluding elemental gold deposited during the reaction.
[0080] Test results are as follows Figure 10 As shown in (a), under light-shielded conditions, the two-dimensional organic material can only bind through simple physicochemical coordination between surface active sites and metal ions, resulting in a limited gold recovery rate of approximately 985 mg / g per unit mass of material. However, under continuous visible light irradiation, the system triggers a strong "photo-driven adsorption-reduction" synergistic mechanism. With increasing initial concentration, the adsorption capacity under light conditions exhibits explosive growth, eventually reaching an equilibrium adsorption capacity of 11204 mg / g. This capacity mutation, more than ten times that under light-shielded conditions, reveals that the continuous injection of photogenerated electrons disrupts the traditional thermodynamic adsorption equilibrium at the solid-liquid interface: the adsorbed tetrachloroaurate anions are rapidly reduced to Au nanocrystals and deposited, thereby continuously releasing or renewing specific binding sites on the surface. This allows the framework material to achieve single-time, extremely high-load gold enrichment without undergoing a desorption step.
[0081] 2. Adsorption-reduction kinetics test In the absence of light and visible light (light source model CEL-S500, light intensity 100 mW / cm²), the light source is protected from light. 2 A comparative test of gold recovery kinetics was conducted under two conditions: 2 mL of an aqueous solution (pH 3) containing 0.4 mg / mL of the two-dimensional organic material prepared in Example 1 was added to 40 mL of potassium chloroaurate solution (concentration of 50 ppm as gold element). Recovery tests were carried out under conditions of light avoidance and continuous visible light irradiation. Samples were taken at fixed intervals to measure the concentration of the remaining tetrachloroaurate anion in the solution (concentration of 50 ppm as gold element), and the corresponding gold recovery rate was calculated. Time-kinetic curves were plotted.
[0082] Test results are as follows Figure 10As shown in (b), the kinetics are very slow in the light-shielded reaction; however, in the light-driven mode, the reduction rate shows a steep linear increase within the first 60 minutes of the reaction, and a high-efficiency recovery of over 99% can be achieved within 90 minutes. This excellent reduction kinetic performance confirms the synergistic advantages of the material's intrinsic structure: its 1.40 eV optical bandgap ensures extremely high photon utilization, while the two-dimensional ultrathin structure significantly shortens the physical distance of charge transfer to the interface, effectively suppressing bulk recombination of photogenerated carriers. This structural feature provides a continuous and ultrafast electron supply at the interface, allowing tetrachloroaurate anions to be rapidly reduced and solidified upon contact with the material surface, greatly shortening the gold extraction process time.
[0083] 3. Selective recycling test of multi-metal coexistence system Gold selective recovery experiments were conducted in a simulated solution containing high concentrations of copper and nickel impurities: a solution containing tetrachloroaurate anions and Cu... 2+ Ni 2+ The simulated solution, with an initial concentration of 222.1 mg / L (based on gold elemental concentration) and Cu... 2+ The concentration was 2727.5 mg / L, Ni 2+ The concentration was 131.13 mg / L. After the recovery reaction was completed by visible light irradiation, the remaining content of each metal element in the solution was measured and the corresponding recovery rate was calculated.
[0084] Test results are as follows Figure 10 As shown in (c), although the concentrations of copper and nickel impurity ions in the system are much higher than those of tetrachloroaurate anions, resulting in strong competitive interference, the recovery rate of gold by the two-dimensional organic material is close to 100%, and the recovery rate of Cu is also high. 2+ Ni 2+ The coprecipitation or reduction rates were both below 10%, demonstrating a high degree of selectivity for tetrachloroaurate anions. This targeted selectivity is not only due to the specific binding of the porphyrin units in the framework to tetrachloroaurate anions, but also to the precise energy level matching between the reduction potential of the photogenerated electrons and the gold complex ion, thus effectively eliminating interference from common high-concentration base metal ions and successfully achieving highly efficient and selective extraction of gold in this impure liquid phase system.
[0085] 4. Phase composition, microstructure, and loading of the products after the photo-driven reduction reaction To further clarify the phase composition, microstructure, and loading of the product after the visible light-driven reduction reaction, the gold-loaded composite product that underwent the reaction in Example 1 was systematically characterized in terms of morphology and structure.
[0086] like Figure 11As shown in the SEM image in (a), after in-situ photoreduction, the generated elemental gold is epitaxially grown on the surface of a two-dimensional organic material, forming an ultrathin hexagonal nanosheet structure with regular morphology and a lateral size of micrometers, and is evenly distributed. Figure 11 The XRD pattern in (b) confirms the crystal structure of the metal product. Extremely sharp characteristic diffraction peaks appear at 2θ of 38.21°, 44.49°, 64.60°, 77.55° and 81.73°, which perfectly correspond to the (111), (200), (220), (311) and (222) crystal planes of standard elemental gold (Au) with face-centered cubic (fcc) structure, respectively. The extremely high peak intensity and the absence of impurity peaks indicate that the reduced elemental gold has excellent crystallinity.
[0087] at the same time, Figure 11 The XPS high-resolution Au 4f spectrum in (c) further pinpointed the chemical valence state of the metal. The fitting results showed that the two strong characteristic peaks with binding energies at 84.0 eV and 87.7 eV belonged to Au 4f, respectively. 7 / 2 and Au 4f 5 / 2 Orbit. This energy level position corresponds to the standard zero-valent gold (Au) orbit. 0 The characteristic peaks of the two atoms are completely consistent, proving that the tetrachloroaurate anion specifically bound to the framework has been completely and in situ reduced to zero-valent elemental gold.
[0088] also, Figure 11 The TG-DTG curve in (d) visually reflects the extremely high gold loading and thermodynamic evolution of this material. During the programmed temperature rise from room temperature to 1000 °C, the total weight loss of the composite system was only about 16.5%. Combined with the DTG curve, it can be seen that the slow weight loss before 400 °C is mainly attributed to the removal of physically adsorbed water and residual solvent within the pores, while the dramatic weight loss peak around 540 °C corresponds to the complete decomposition of the two-dimensional organic supramolecular backbone. At the end of the test, the constant residual mass of up to 83.5% represents elemental gold with extremely high thermal stability. The mass conversion results of this batch of samples conclusively demonstrate that the two-dimensional organic material of this invention has excellent enrichment and high-load reduction capabilities for specific gold complex ions, providing the most direct data support for the application of this material in actual gold extraction processes.
[0089] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A two-dimensional organic material, characterized in that, The two-dimensional organic material is a two-dimensional nanosheet formed by supramolecular self-assembly of protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin and pyromellitic acid. The two-dimensional organic material was prepared by the following method: (1) Dissolve 5,10,15,20-tetra(4-aminophenyl)porphyrin in an acid solution, wherein the concentration of 5,10,15,20-tetra(4-aminophenyl)porphyrin in the acid solution is 0.8-1.2 mg / mL, to obtain a protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin solution; dissolve pyromellitic acid in water to obtain a pyromellitic acid aqueous solution with a concentration of 0.8-1.2 mg / mL; (2) The protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin solution, the pyromellitic acid aqueous solution and water are mixed at a volume ratio of (1.3-1.4):1:(97-100) and self-assembled at 48-52 °C to obtain the two-dimensional organic material.
2. The two-dimensional organic material according to claim 1, characterized in that, The two-dimensional organic material includes single-layer two-dimensional nanosheets, double-layer two-dimensional nanosheets, and 3-10 layers of two-dimensional nanosheets; the thickness of the single-layer two-dimensional nanosheets is 1.3-2.0 nm, the thickness of the double-layer two-dimensional nanosheets is 3.0-4.0 nm, and the lateral dimension of the two-dimensional organic material is 10-20 μm.
3. The two-dimensional organic material according to claim 1 or 2, characterized in that, The optical band gap of the two-dimensional organic material is 1-2 eV.
4. A method for preparing a two-dimensional organic material according to any one of claims 1-3, characterized in that, It consists of the following steps: (1) Dissolve 5,10,15,20-tetra(4-aminophenyl)porphyrin in an acid solution, wherein the concentration of 5,10,15,20-tetra(4-aminophenyl)porphyrin in the acid solution is 0.8-1.2 mg / mL, to obtain a protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin solution; dissolve pyromellitic acid in water to obtain a pyromellitic acid aqueous solution with a concentration of 0.8-1.2 mg / mL; (2) The protonated 5,10,15,20-tetra(4-aminophenyl)porphyrin solution, the pyromellitic acid aqueous solution and water are mixed at a volume ratio of (1.3-1.4):1:(97-100) and self-assembled at 48-52 °C to obtain the two-dimensional organic material.
5. The preparation method according to claim 4, characterized in that, In step (1), the concentration of the acid solution is 0.10-0.14 mol / L.
6. The application of the two-dimensional organic material according to any one of claims 1-3 in gold recycling.
7. A method for recovering gold from a gold-containing solution using the two-dimensional organic material according to any one of claims 1-3, characterized in that, Includes the following steps: S1. The two-dimensional organic material is mixed with a gold-containing solution and subjected to an adsorption-reduction synergistic reaction under visible light irradiation. Under photoexcitation, the two-dimensional organic material uses photogenerated electrons to reduce the specifically bound tetrachloroaurate anions to elemental gold in situ and deposit it on the surface of the two-dimensional organic material. S2. Solid-liquid separation is performed on the two-dimensional organic material deposited with elemental gold to separate and extract the elemental gold, thereby realizing the recovery of gold.
8. The method according to claim 7, characterized in that, In step S1, the pH value of the gold-containing solution is 2-7.
9. The method according to claim 7, characterized in that, In step S1, the wavelength of the visible light is 400-800nm.
10. The method according to claim 7, characterized in that, In step S1, the intensity of the visible light is 10-100 mW / cm². 2 .
Citation Information
Patent Citations
Boron-doped carbon nitride / cobalt porphyrin metal organic framework composite photocatalyst and preparation method thereof
CN114887642A
Electron-rich copper site layered supramolecular photocatalytic material as well as preparation and application thereof
CN121372508A
